Knowledge, Attitude and Practice of Dentists Towards Provision of Dental Care to Pregnant Women (Indian Journal of Public Health Research & Development, 2020)
Aim : The objective of this study was to evaluate the knowledge, attitude and practice of dentists towardsprovision of dental care to pregnant women.Material and Method: A multiple choice questionnaire was self-administered to dentists in Chennai. Thecollected data was statistically analysed.Results: Although majority of the dentists were well informed about the management of pregnant patients,dilemmatic attitudes were seen regarding dental radiographs, local anaesthesia and prenatal fluoridesupplementation.Conclusion: This demonstrates the need to broaden the knowledge of dental surgeons via CDE programsand workshops.
Keywords: Oral health, pregnancy, dentists, knowledge, drugs, radiographs.